Kontribusi Creative Dance dalam Menumbuhkan Karakter Anak Merdeka - Purnama Sari, Dyan Indah; Indriyanti, Poppy; Yulianti, Ratna (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2021)
Creative Dance or Experience Dance is a conceptual dance learning model that is oriented towards freedom of expression and creativity. The freedom of expression and movement in Creative Dance is relevant to the substance of creativity which emphasizes individual awareness in expressing their creative imaginative abilities. Children who get freedom of expression are creative self-determined children. Creative Dance in the process is able to manage children's thought patterns and behavior patterns that are projected through several creative processes such as exploration, improvisation, deconstruction, construction, and reconstruction. This creative process is what will produce high human values ??in the soul of the children. Therefore, this research will analyze the results and contribution of the application of the Creative Dance model in phase 1 children, that is the early childhood to the elementary school-age children in the city of Bandung (Semesta Tari Bandung Community) and Yogyakarta (PGSD UST). Semesta Tari Bandung Community is one of the alternative education communities in the field of dance that has carried the Creative Dance model as a learning method since 2014, and Ratna Yulianti, S. Sn., M. Sd is the initiator of the Semesta Tari community as well as one of the observers of art education especially in early childhood and elementary schools in Indonesia. This collaborative research is expected to produce product outputs in the form of models, and scientific papers that can be useful for the public. This research was conducted online from Yogyakarta and Bandung. This type of research is qualitative research using descriptive analysis method which aims to describe, summarize various conditions, various situations, or various phenomena of social realities that exist in society. Data collection techniques used are observation, interviews, and documentation. Keywords: Creative Dance, Creative-Imitative, Self-Determination Child Characteristics